Photochemical Upconversion Light Emitting Diode (LED): Theory of Triplet Annihilation Enhanced by a Cavity. Issue 1 (20th September 2018) - Frazer, Laszlo
Abstract: Artificial lighting is a widespread technology which consumes large amounts of energy. Triplet–triplet annihilation photochemical upconversion is a method of converting light to a higher frequency. Here, it is shown theoretically that photochemical upconversion can be applied to Watt‐scale lighting, with performance closely approaching the 50% quantum yield upper limit. The dynamic equilibrium of an efficient device consisting of an LED, an upconverting material, and an optical cavity is described from optical and thermal perspectives. Abstract : Photochemical upconversion can shift the spectrum of light to a higher energy. Here, the efficiency of lighting based on upconversion is predicted. The presented model uses optical, kinetic, and thermal properties to calculate the wall‐plug efficiency of an upconversion system. Temperature management is essential to efficient operation.